A Comparison on Biodiversity between Private Conservation and Wildlife Reserve Forests in Riau by using Macro-moths as an Indicator - HARI SUTRISNO (Society for Indonesian Biodiversity, 2009)
A study on biodiversity of the two forest management types, private conservation forest PT. A and wildlife reserve forest of Suaka Margasatwa Giam Siak Kecil, Riau by using a rapid assessment approach with macro-moths as an indicator wasconducted from 23 October to 6 November 2007. Four sample sites were established in Giam Siak Kecil Wildlife Reserve,whereas three sample sites were performed in private conservation forest PT. A. The results show that the diversity indexes based on Fisher’s α of the private forest PT. A was higher than those of wildlife reserve forest Giam Siak Kecil, they were 67.98 and 47.86, respectively. The species composition of the two forests is different, pyralid moths dominate at Giam Siak Kecil. On the contrary, Geometrid moths dominate at private conservation forest PT. A. The results indicated that diversity index and species composition in Giam Siak Kecil is influenced by habitat changes and decrease on floral diversity due to illegal logging. Moreover, a low faunal similarity which is indicated by Jaccard’s index that is only 0.218 showed that thesamples represent significant different communities.Key words: biodiversity, conservation, macro-moths, Fisher’s α index